Online Media Framing of Mining Permit Policies of Religious Mass Organizations (Ormas): A Study on Detik.com and Kompas.com - Maududi, Mukhlish Muhammad; Ramadlan, Said; Digdoyo, Eko (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2025)
Government policy granting mining management permits to religious mass organizations (ormas) has sparked a range of public responses and has become a sensitive issue that is widely covered by the media. This study aimed to analyze how online media framing shapes public discourse regarding policy, particularly through coverage by Detik.com and Kompas.com. The research employs a qualitative approach using Entman’s framing analysis model, which includes four elements: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. Data were collected from 58 news articles published between May and July of 2024 (26 from Detik.com and 32 from Kompas.com). The analysis technique involved content categorization and narrative interpretation of each framing element. The results show that Detik.com tends to frame the issue in a neutral and procedural manner, predominantly featuring elite quotations, without exploring conflicts or making moral judgments. By contrast, Kompas.com presents a more reflective and deliberative framing, highlighting internal disagreements within the ormas and drawing attention to the moral, environmental, and social aspects of mining policy. This difference in framing reflects each media outlet’s editorial orientation and position within the media power structure. These findings underscore that online media is not homogeneous and that news framing can shape diverse public perceptions and discourses about state policies. This study contributes to the scholarly examination of digital media framing in Indonesia, in the context of differing perspectives and societal narratives regarding state policies and natural resources. Keywords: Entman, framing, mining, Muhammadiyah ABSTRAKKebijakan pemerintah yang memberikan izin pengelolaan tambang kepada organisasi masyarakat (ormas) keagamaan menimbulkan beragam respons publik dan menjadi isu sensitif yang diliput luas oleh media. Penelitian ini bertujuan untuk menganalisis bagaimana framing media online membentuk wacana publik atas kebijakan tersebut, khususnya melalui pemberitaan Detik.com dan Kompas.com. Penelitian ini menggunakan pendekatan kualitatif dengan analisis framing model Entman yang mencakup empat elemen: define problems, diagnose causes, make moral judgment, dan suggest remedies. Data diambil dari 58 berita yang terbit pada Mei–Juli 2024 (26 dari Detik.com dan 32 dari Kompas.com). Teknik analisis dilakukan dengan kategorisasi isi dan interpretasi naratif per elemen framing. Hasil penelitian menunjukkan bahwa Detik.com cenderung membingkai isu secara netral dan prosedural, dengan dominasi kutipan elite tanpa eksplorasi konflik atau penilaian moral. Sebaliknya, Kompas.com menunjukkan framing yang lebih reflektif dan deliberatif, dengan mengangkat perbedaan pendapat internal ormas, serta menyoroti aspek moral, lingkungan, dan sosial dari kebijakan tambang. Perbedaan framing ini mencerminkan orientasi redaksional masing-masing media serta posisi mereka dalam struktur kekuasaan media. Temuan ini menegaskan bahwa media online tidak bersifat homogen, dan framing berita dapat membentuk persepsi serta wacana publik yang beragam atas kebijakan negara. Penelitian ini memberikan kontribusi pada kajian framing media digital di Indonesia dalam konteks perbedaan pandangan dalam narasi dan perspektif masyarakat tentang Kebijakan Negara dan sumber daya ala.Kata Kunci: Entman, framing, tambang, Muhammadiyah